Pen of Iron : American Prose and the King James Bible - Alter, Robert (Book collections on Project MUSE., 2010)
In this book, biblical translator and literary critic Robert Alter traces some of the fascinating ways that American novelists--from Melville, Hemingway, and Faulkner to Bellow, Marilynne Robinson, and Cormac McCarthy--have drawn on the rich stylistic resources of the canonical English Bible to fashion their own strongly resonant styles and distinctive visions of reality. --from publisher description.